Kandungan gizi dan manfaat pada buah naga lokal untuk kesehatan - Putri, Awalina Nazalia (Maliki Interdisciplinary Journal, 2024)
Dragon fruit (Hylocereus poiyrhizus) is a tropical and subtropical fruit that is currently widely cultivated in Indonesia, Taiwan, Vietnam, Malaysia and the Philippine. Red dragon fruit is one of the local fruits that has health potential. This study aims to analyze the nutritional content and health benefits of local Indonesian red dragon fruit varieties. The research was carried out with a literature study of a variety of scientific information and supporting data that came from previous research related to the nutritional composition of the local dragon fruit. The results showed that lical red dragon fruit contains vitanin C , B complex vitamins, fiber, minerals such as calcium and phosphorus , as well as phenolic and flavonoid compounds that act as antioxidants. This nutritional content has the potential to provide health benefits such as preventing degenerative diseases, increasing body immunity, and lowering blood cholesterol. Thus, consumption of local red dragon fruit can be part of a healthy lifestyle for the community. Keywords: local red dragon fruit, antioxdant, health benefits